Crisis Management of Negative Publicity on Waste Management in Yogyakarta (A Study of the Handling of Negative Publicity Related to Waste by the Yogyakarta City Tourism Office as a Tourism Destination) - Muhammadian Rassief Shiddiq; Aswad Ishak (Jogjakarta Communication Conference (JCC), 2025)
Crisis handling of negative news related to waste that is rampant in the city of Yogyakarta, affecting the Yogyakarta City Tourism Office to gain a negative image in the eyes of the public. The purpose of this research is to find out how the Yogyakarta City Tourism Office handles this problem. This research uses a qualitative approach with a case study method, where data is collected through in-depth interviews and data validation tests. The results obtained show that the waste management news faced by the Yogyakarta City Tourism Office is not the only problem. The crisis that occurred began with the emergence of various kinds of negative comments on the condition of the City of Yogyakarta. The conclusion of this research highlights the Yogyakarta City Tourism Office, how to handle negative news related to waste that can make the image of the Yogyakarta City Tourism Office even worse. The lack of dedication that is done makes it even murkier, from the view of local residents and even foreign tourists. This research was conducted to keep the reputation or image of the Yogyakarta City Tourism Office from getting worse, and Yogyakarta as a tourist destination.